Real-world efficacy of the Hydrus microstent in Black and Afro-Latinx patients with glaucoma: a retrospective study. - Laroche, Daniel; Nkrumah, Gideon; Ng, Chester (Therapeutic Advances in Ophthalmology, 2020)
Purpose: The purpose was to determine the real-world efficacy of phacoemulsification cataract surgery and Hydrus microstent in Black and Afro-Latinx patients with glaucoma. Methods: A retrospective noncomparative single-center study of 76 Black and Afro-Latinx patients with glaucoma who underwent phacoemulsification cataract surgery and Hydrus microstent placement for treatment of glaucoma at single practice. Investigated parameters were intraocular pressure (IOP), number of medications, mean deviation on visual field test, and visual acuity. Patients were also subgrouped into mild, moderate, and advance glaucoma for further analysis. Results: We reviewed a total of 76 patients who had 6 months of follow up in the study. The mean number of medications decreased significantly from 2.6 ± 1.5 preoperatively to 0.72 ± 1.4 in 6 months (p < 0.0010), while IOP decreased from 14.7 ± 3.7 to 13.9 ± 4.3 (p = 0.25). At 6 months, 55 patients (74%) of all patients were medication free (n = 27, 84.4% mild glaucoma; n = 17, 70.8% moderate glaucoma; n = 10, 50% advance glaucoma). There was significant improvement in visual acuity (p < 0.00010) and stabilization of mean deviation on visual field test (baseline −9.2; 6 months −9.1; p = 0.22). The most common adverse effect was a transient IOP spike and transient corneal edema (n = 6, 7.9%; n = 6, 7.9%, respectively) with spontaneous resolution in all cases. No sight-threatening complications were reported at 6 months. Conclusion/clinical relevance: This 6-month retrospective study demonstrated the efficacy of phacoemulsification cataract surgery and Hydrus microstent in reducing the medication burden while maintaining lower IOP in Black and Afro-Latinx patients with glaucoma.